RECORD OF HEMIPTERAN INSECT PEST DIVERSITY ON RECORD OF HEMIPTERAN INSECT PEST DIVERSITY ON RECORD OF HEMIPTERAN INSECT PEST DIVERSITY ON MURRAYA KOENIGII OENIGII (L.) SPRENGEL (CURRY LEAF), A MEDICINALLY IMPORTANT PLANT FROM J ANT PLANT FROM JAMMU REGION - J. S. TARA,; MONIKA SHARMA, (The Bioscan, 2010)
Curry leaf (Murraya koenigii), a member of family Rutaceae is a semi-deciduous, aromatic pubescent shrub or a small sub-tropical tree used both as a food ingredient as well as in medicines. Leaves, seeds, bark, flowers and root of the plant are reported to contain lots of minerals and essential oils of immense medicinal value. Species diversity analyzed through consistent survey and sampling conducted in various districts of Jammu region from March 2008 to Feb. 2009 indicated that the curry leaf plantations are damaged mostly by insects belonging to order Hemiptera. A total of 8 insect species belonging to 7 different families of order Hemiptera were recorded to infest curry leaf plantations in different districts of Jammu region.